Solar-driven water treatment re-engineering and accelerating nature's water cycle - Mahian, Omid; Wei, Jinjia; Taylor, Robert A.; Wongwises, Somchai (Academic Press, 2021)
Solar-Driven Water Treatment: Re-engineering and Accelerating Nature's Water Cycle looks at the use of solar energy and in particular photovoltaic technologies, as a viable, accessible and sustainable option in the treatment of water. Solar-Driven Water Treatment: Re-engineering and Accelerating Nature's Water Cycle provides insight into the different solar powered technologies, in-depth information about the viability of sunlight in the water treatment process, the potential environmental implications as well as the performance, economics, operation and maintenance of the discussed technologies. Elaborating on the potential issues and health risks associated with the water purification systems this reference also covers the need for appropriate technologies in the present scenario to improve worldwide access to clean drinking water. Readers will learn the most appropriate technology for their specific need making this book useful for renewable energy and environmental engineers in investigating energy efficiency, water treatment technologies, and the economics of technological change in the treatment of water by solar technologies.